Open Posterolateral Ligament Plication and Lateral Ulnar Collateral Ligament Repair in Posterolateral Rotatory Instability of the Elbow Using an All-Suture Construct - Michell Ruiz Suarez, M.D., Ph.D.; José Eduardo Torres Rangel, M.D.; Rafael Gamba Galeazzi, M.D.; Andrés Felipe Cobaleda Aristizabal, M.D. (Arthroscopy Techniques)
Posterolateral rotatory instability of the elbow is the most common form of lateral-sided instability; it is often the result of an injury to the lateral collateral ligament complex involving the lateral ulnar collateral ligament. Recently, the posterolateral capsule of the elbow has been recognized to play a major role in preventing posterolateral rotatory instability, identifying it as an independent ligament of the lateral complex (posterolateral ligament). We present our technique for posterolateral elbow stabilization through plication of the posterolateral ligament associated with repair of the lateral ulnar collateral ligament using an all-suture anchor.